Activating p53 family member TAp63: A novel therapeutic strategy for targeting p53‐altered tumors. Issue 14 (23rd April 2019) - Gunaratne, Preethi H.; Pan, Yinghong; Rao, Abhi K.; Lin, Chunru; Hernandez‐Herrera, Anadulce; Liang, Ke; Rait, Antonina S.; Venkatanarayan, Avinashnarayan; Benham, Ashley L.; Rubab, Farwah; Kim, Sang Soo; Rajapakshe, Kimal; et al.
Abstract : Background: Over 96% of high‐grade ovarian carcinomas and 50% of all cancers are characterized by alterations in the p53 gene. Therapeutic strategies to restore and/or reactivate the p53 pathway have been challenging. By contrast, p63, which shares many of the downstream targets and functions of p53, is rarely mutated in cancer. Methods: A novel strategy is presented for circumventing alterations in p53 by inducing the tumor‐suppressor isoform TAp63 (transactivation domain of tumor protein p63 ) through its direct downstream target, microRNA‐130b (miR‐130b), which is epigenetically silenced and/or downregulated in chemoresistant ovarian cancer. Results: Treatment with miR‐130b resulted in: 1) decreased migration/invasion in HEYA8 cells ( p53 wild‐type) and disruption of multicellular spheroids in OVCAR8 cells ( p53 ‐mutant) in vitro, 2) sensitization of HEYA8 and OVCAR8 cells to cisplatin (CDDP) in vitro and in vivo, and 3) transcriptional activation of TAp63 and the B‐cell lymphoma ( Bcl )‐inhibitor B‐cell lymphoma 2‐like protein 11 ( BIM ). Overexpression of TAp63 was sufficient to decrease cell viability, suggesting that it is a critical downstream effector of miR‐130b. In vivo, combined miR‐130b plus CDDP exhibited greater therapeutic efficacy than miR‐130b or CDDP alone. Mice that carried OVCAR8 xenograft tumors and were injected with miR‐130b in 1, 2‐dioleoyl‐sn‐glycero‐3‐phosphatidylcholine (DOPC) liposomes had a significant decrease in tumor burden at rates similar to those observed in CDDP‐treated mice, and 20% of DOPC–miR‐130b plus CDDP‐treated mice were living tumor free. Systemic injections of scL–miR‐130b plus CDDP in a clinically tested, tumor‐targeted nanocomplex (scL) improved survival in 60% and complete remissions in 40% of mice that carried HEYA8 xenografts. Conclusions: The miR‐130b/ TAp63 axis is proposed as a new druggable pathway that has the potential to uncover broad‐spectrum therapeutic options for the majority of p53 ‐altered cancers. Abstract : This study uncovered a new feed‐forward loop that involves tumor protein p53 family member TAp63 and its downstream target microRNA 130b (miR‐130b). Injection of miR‐130b using 1, 2‐dioleoyl‐sn‐glycero‐3‐phosphocholine liposomes (nontargeted) and a clinically tested, tumor‐targeted nanocomplex (scL) resulted in significantly decreased tumor burden and improved overall survival, suggesting that the miR‐130b/TAp63 tumor‐suppressor axis could open up novel therapeutic options for many cancers with alterations in the p53 gene and/or pathway.